Community Weight Loss to Combat Obesity and Disability in At-Risk Older Adults - Rejeski, W Jack (J Gerontol A Biol Sci Med Sci, 2017)
BACKGROUND: Among older, overweight, and obese adults with either cardiovascular disease or the metabolic syndrome, reduced mobility and loss of leg strength are important risk factors for morbidity, disability, and mortality. It is unclear whether community-based approaches to weight loss may be an effective solution to this public health challenge. METHODS: An 18-month three-site, randomized controlled trial conducted by YMCA staff, with blinded assessors, enrolled 249 older, overweight, and obese adults with either cardiovascular disease or metabolic syndrome with randomization to three interventions: weight loss alone (WL), weight loss + aerobic training (WL + AT), and weight loss + resistance training (WT + RT). The dual primary outcomes were 400-m walk time in seconds and knee extensor strength in Newton meters. RESULTS: All groups lost weight from baseline: average baseline adjusted change of −6.1% (95% confidence interval [CI]: −7.5 to −4.7) for WL only, −8.6% (95% CI: −10.0 to −7.2) for WL + AT, and −9.7% (95% CI: −11.1 to −8.4) for WL + RT. Combined, the two physical activity + WL training groups had greater improvement in walk time than WL alone (mean difference 16.9 seconds [95% CI: 9.7 to 24.0], p < .0001). Baseline adjusted change in knee extensor strength was no greater with WL + RT than WL + AT (mean difference −3.6 Nm [95% CI: −7.5 to 0.3], p = .07). CONCLUSIONS: At risk, older, overweight and obese adults can achieve clinically significant reductions in body weight with community-based weight loss programs. The change in percent weight loss and improvements in mobility are significantly enhanced when either RT or AT is combined with dietary WL.